Kaempferol protects against high-salt-induced hypertension and vascular endothelial injury by inhibiting ferroptosis through the ATF4/ACSL4 pathway - Qiuer Liang; Minghao Chen; Guangtian Chen; Pengli Xu; Lai Kwan Lam; Pengcheng Xie; Ting Xie; Wanqing Tu; Tianhao Liu; Xiaopeng Peng; Haoyao Yuan; Liguo Chen; et al. (Journal of Functional Foods)
To date, no specific treatments have been developed for high-salt-induced hypertensive vascular damage, emphasizing the need to elucidate its underlying molecular mechanisms for therapeutic innovation. Kaempferol (Kae), a natural flavonol belonging to the flavonoid family, has demonstrated significant vascular protective effects in previous studies. However, its impact on high-salt-induced hypertensive vascular injury remains unclear. This study aimed to explore the pharmacological effects and underlying mechanisms of Kae in mitigating hypertensive vascular damage. Using an 8 % high-salt diet model, we evaluated the effects of Kae (200 mg/kg/day) in wild-type (WT) and activating transcription factor 4 (ATF4+/−) knockout mice. Additionally, human aortic endothelial cells (HAECs) cultured under high-salt conditions were used to assess Kae's protective effects, with ATF4 and acyl-CoA synthetase long-chain family member 4 (ACSL4) knocked down via siRNA transfection. Our results showed that Kae significantly reduced high-salt-induced hypertension, improved vascular endothelial dysfunction, inhibited ferroptosis, and suppressed ATF4 expression. Compared to ATF4+/−mice on a high-salt diet, ATF4+/−mice treated with Kae exhibited greater reductions in blood pressure and endothelial damage and more pronounced inhibition of ferroptosis. Surface plasmon resonance and molecular docking analyses revealed that Kae directly binds to ATF4, while proteome microarray and co-immunoprecipitation assays demonstrated that ATF4 interacts with ACSL4 in HAECs. Furthermore, inhibition of ATF4 or ACSL4 effectively alleviated endothelial ferroptosis induced by high-salt stress. In summary, our findings suggest that Kae mitigates high-salt-induced hypertension by inhibiting endothelial ferroptosis via the ATF4/ACSL4 pathway, providing a potential therapeutic strategy for hypertensive vascular injury.